Solar-heat-assisted hydrogen production using solid oxide electrolysis cells in Japan - Tanaka, Yohei; Roeder, Timo; Monnerie, Nathalie (Frontiers in Energy Research, 2025)
Japan and other industrialized countries rely on the import of green hydrogen (H2) as they lack the resources to meet their own demand. In contrast, countries such as Australia have the potential to produce hydrogen and its derivatives using wind and solar energy. Solar energy can be harnessed to produce electricity using photovoltaic systems or to generate thermal energy by concentrating solar irradiation. Thus, thermal and electrical energy can be used in a solid oxide electrolysis process for low-cost hydrogen production. The operation of a solid oxide electrolysis cell (SOEC) stack integrated with solar energy is experimentally investigated and further analyzed using a validated simulation model. Furthermore, a techno-economic assessment is conducted to estimate the hydrogen production costs, including the expenses associated with liquefaction and transportation from Australia to Japan. High conversion efficiencies and low-cost SOECs are projected to result in production costs below 4 USD/kg.